2006
DOI: 10.2208/jsceseee.23.109s
|View full text |Cite
|
Sign up to set email alerts
|

Two-Level Seismic Design Method Using Post-Yield Stiffness and Its Application to Unbonded Bar Reinforced Concrete Piers

Abstract: The two-level seismic design method using post-yield stiffness is proposed. The post-yield stiffness on the load-displacement relationship of the RC pier is found to be effective for the reduction of both the demand strength and the residual displacement under extreme earthquakes. Then, the two-level seismic design method is applied to the Unbonded Bar Reinforced Concrete (UBRC) pier that has the stable postyield stiffness. The smaller cross section is designed than the optimal cross section of the conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…To examine structural performance, the full-scale model of the structure was simulated by numerical analysis. This study refers to the reference design of Iemura et al 21) which the designed conventional reinforced concrete structures following JRA code 3) was applied as a benchmark of the proposed structure. The bridge pier properties are 9.6 m in height, 507 tons of superstructure mass, 5.0 of the ductility factor.…”
Section: ) the Structural Performance Investigation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To examine structural performance, the full-scale model of the structure was simulated by numerical analysis. This study refers to the reference design of Iemura et al 21) which the designed conventional reinforced concrete structures following JRA code 3) was applied as a benchmark of the proposed structure. The bridge pier properties are 9.6 m in height, 507 tons of superstructure mass, 5.0 of the ductility factor.…”
Section: ) the Structural Performance Investigation Methodsmentioning
confidence: 99%
“…The conventional RC pier was simulated to make structural performance comparisons. In this study, there are two types of conventional structures, the structure that followed the reference 21) was varied with different reinforcing steel grades, namely SD345 and USD685.…”
Section: ) the Structural Performance Investigation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ruiz‐García and Miranda [ 2 ] found that the maximum inelastic deformation of bilinear systems with a positive second stiffness was smaller, with respect to the elastoplastic system. Iemura et al [ 3 ] found that the second stiffness of structures was effective for the reduction of both the demand of strength and the residual displacement under extreme earthquakes. Ye et al [ 4 ] studied single degree of freedom (SDOF) and multidegree of freedom (MDOF) systems to investigate the influence of second stiffness on the inelastic seismic response.…”
Section: Introductionmentioning
confidence: 99%